THE PRESENCE OF AEDES HENDERSONI IN MEXICO - Ortega-Morales, Aldo I; Rodríguez-Rojas, Jorge J; Fernández-Santos, Nadia A; Medrano-Santillana, Miguel; Ayala-Sulca, Yuri O; Arque-Chunga, Wilfredo; Colos-Galindo, Percy; Ortega-Morales, Natalia B; López-Hernández, Isaías; Rodríguez-Pérez, Mario A (Journal of the American Mosquito Control Association, 2025)
The mosquito species commonly named Henderson American pointy mosquito, Aedes hendersoni, was found during a routine mosquito vector surveillance from 2020 to 2023 in diverse collection sites with conserved forested vegetation at the Eco-Parks Rincón de la Silla and El Salto in Nuevo León, northeastern Mexico. Collected specimens were labeled, mounted, and identified using taxonomic keys. Further confirmation of Ae. hendersoni was performed by deoxyribonucleic acid (DNA) barcoding and cytochrome oxidase-I (COI) sequences served to confirm the identity of Ae. hendersoni by comparison with other sequences of species with Triseriatus group and Protomacleaya subgenus of Aedes. Voucher specimens were curated and are available in 2 Mexican collection repositories and COI sequences were deposited in the NCBI GenBank with accession number MG242473.1. Hence, the presence of Ae. hendersoni in México is documented for the first time. Now, geographic occurrence of this species is from Canada throughout United States to northeastern México. With this new record, there are the 4 mosquito species in the Triseriatus group [Aedes: (Protomacleaya)] and 252 species in México.